Profil Literasi Donor Darah pada Kalangan Mahasiswa Gen Z di Yogyakarta - Rendi Sinanto; Magdalena Sohilait (PT. Promosi Kesehatan Media, 2026)
Background: Indonesia's national blood supply still faces a structural deficit of 1.5 million bags per year. Generation Z (Gen Z) students are positioned as the primary target for addressing this shortage, but their participation is hampered by low blood donor literacy and psychological factors. This study aims to determine the Blood Donor Literacy Profile among Gen Z students in Yogyakarta by shifting the paradigm from traditional cognitive testing to mapping modern, gender-responsive health literacy. Methods: This study involved a population of 207 individuals, with a purposive sampling technique involving 68 respondents. The research instrument used a questionnaire that had previously been validated. Data analysis was conducted using univariate analysis with a frequency distribution. Results and Discussion: The results indicate that the respondents were predominantly male (51.5%) compared to female (48.5%). From a cognitive perspective, no respondents (0%) were found with insufficient knowledge; the entire sample was evenly divided into the good (50%) and sufficient (50%) categories. However, there was a cognitive asymmetry, with females outperforming males in the good knowledge category (26.4% compared to 23.5%). This was influenced by female students' higher health consciousness and critical approach to filtering online information, while male students tended to be pragmatic and less aware of the long-term biological benefits of blood donation. Conclusion: This study's conclusions confirm that digital blood donation campaign strategies on campus should be designed asymmetrically; the approach for male students emphasizes direct digital push marketing based on concrete actions, while for female students, it focuses on strengthening donor nutrition literacy.